Thickening of the pituitary stalk in children and adolescents with central diabetes insipidus: Causes and consequences - Beatriz Corredor Andrés; María Teresa Muñoz Calvo; Miguel Ángel López Pino; María Márquez Rivera; Lourdes Travieso Suárez; Jesús Pozo Román; Jesús Argente (Elsevier, 2019)
Background: Central diabetes insipidus (CDI) is a rare disorder in children. The aetiology of CDI in childhood is heterogeneous. The aim of this study is to illustrate the importance of a careful clinical and neuro-radiological follow-up of the pituitary and hypothalamus region in order to identify the aetiology and the development of associated hormonal deficiencies. Methods: Clinical and auxological variables of 15 children diagnosed with CDI were retrospectively analysed in a paediatric hospital. Evaluations of adenohypophyseal function and cranial MRI were performed periodically. Results: The mean age at diagnosis of CDI was 9.6 years (range: 1.32-15.9). The aetiological diagnosis could be established initially in 9 of the 15 patients, as 7 with a germinoma and 2 with a histiocytosis. After a mean follow-up of 5.5 years (range: 1.6-11.8), the number of idiopathic cases was reduced by half. At the end of the follow-up, the aetiological diagnoses were: 9 germinoma (60%), 3 histiocytosis (20%), and 3 idiopathic CDI (20%). There is a statistically significant association between stalk thickening and tumour aetiology. At least one adenohypophyseal hormonal deficiency was found in 67% of cases, with the majority developing in the first two years of follow-up. Growth hormone deficiency (60%) was the most prevalent. Conclusion: The follow-up of CDI should include hormone evaluation with special attention, due to its frequency, to GH deficiency. In addition, a biannual MRI in an idiopathic CDI should be performed, at least during the first 2-3 years after diagnosis, as 50% of them were diagnosed with a germinoma or histiocytosis during this period. Resumen: Introducción: La diabetes insípida central (DIC) es una entidad poco frecuente en la edad pediátrica, siendo su etiología heterogénea. El objetivo de nuestro trabajo es demostrar que el seguimiento clínico y neurorradiológico de la región hipotálamo-hipofisaria, puede ayudar a establecer el diagnóstico etiológico de DIC y la presencia de otros déficits hormonales. Métodos: Se revisaron de forma retrospectiva 15 pacientes diagnosticados de DIC en un hospital pediátrico. Se analizaron las características clínicas y auxológicas; así como la valoración de la función adenohipofisaria junto con RM craneal de manera periódica. Resultados: La mediana de edad al diagnóstico fue de 9,6 años (rango: 1,3-15,9). El diagnóstico etiológico pudo establecerse en 9 de los 15 pacientes (germinomas: 7 e histiocitosis: 2). Tras una mediana de seguimiento de 5,5 años (rango: 1,6-11,8), los casos idiopáticos se redujeron a la mitad. Finalmente, los diagnósticos etiológicos fueron: germinoma 9 (60%), histiocitosis 3 (20%) y DIC idiopática 3 (20%). Existe una asociación estadísticamente significativa entre el engrosamiento del tallo y la etiología tumoral. El 67% desarrolló, al menos, una deficiencia hormonal adenohipofisaria, la mayoría en los dos primeros años de seguimiento. El déficit más prevalente fue el de hormona de crecimiento (60%). Conclusiones: En todos los pacientes con DIC se deberá realizar un control auxológico y hormonal, con especial atención, por su frecuencia, a la deficiencia de GH, y en aquellos con DIC idiopática se debería incluir una RM semestral, al menos durante los 2-3 primeros años después del diagnóstico, pues en nuestro estudio el 50% fueron diagnosticados de germinomas o histiocitosis en este periodo.